Leptin Receptor, a Surface Marker for a Subset of Highly Engrafting Long-term Functional Hematopoietic Stem Cells - Trinh, Thao (Leukemia, 2020)
The hematopoietic system is sustained by a rare population of hematopoietic stem cells (HSCs), which emerge during early embryonic development and then reside in the hypoxic niche of the adult bone marrow microenvironment. Although leptin receptor (Lepr)-expressing stromal cells are well-studied as critical regulators of murine hematopoiesis, the biological implications of Lepr expression on HSCs remain largely unexplored. We hypothesized that Lepr(+)HSCs are functionally different from other HSCs. Using in vitro and in vivo experimental approaches, we demonstrated that Lepr further differentiates SLAM HSCs into two distinct populations; Lepr(+)HSCs engrafted better than Lepr(−)HSCs and self-renewed more extensively as noted in secondary transplants. Molecularly, Lepr(+)HSCs were characterized by a proinflammatory transcriptomic profile enriched for Type-I Interferon and Interferon-gamma (IFN-γ) response pathways, which are known to be critical for the emergence of HSCs in the embryo. We conclude that although Lepr(+)HSCs represent a minor subset of HSCs, they are highly engrafting cells that possess embryonic-like transcriptomic characteristics, and that Lepr can serve as a reliable marker for functional long term HSCs, which may have potential clinical applicability.